2019
DOI: 10.1101/752782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Pan-genome Mapping and pairwise SNP-distance improve Detection of Mycobacterium tuberculosis Transmission Clusters

Abstract: Next-generation sequencing based base-by-base distance measures have become an integral complement to epidemiological investigation of infectious disease outbreaks. This study introduces PANPASCO, a computational pan-genome mapping based, pairwise distance method that is highly sensitive to differences between cases, even when located in regions of lineage specific reference genomes. We show that our approach is superior to previously published methods in several datasets and across different Mycobacterium tub… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Raw reads were subjected to quality control with Trimmomatic [12] and Flash [13]. The trimmed and filtered reads were mapped to two different reference genomes: the M. tuberculosis H37Rv strain and a pan-genome reference built from 146 M. tuberculosis genomes [14, 15] with bwa mem [16]. Duplicated reads were marked and reads with mapping quality less than 10 were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw reads were subjected to quality control with Trimmomatic [12] and Flash [13]. The trimmed and filtered reads were mapped to two different reference genomes: the M. tuberculosis H37Rv strain and a pan-genome reference built from 146 M. tuberculosis genomes [14, 15] with bwa mem [16]. Duplicated reads were marked and reads with mapping quality less than 10 were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…We used PANPASCO [15] to calculate relative pairwise SNP distance between all isolates classified as MDR-TB or XDR-TB in the public and German dataset. This method builds on two parts to enable distance calculation for large, diverse datasets: mapping all reads to a computational pan-genome including 146 M. tuberculosis genomes and distance calculation for each individual pair of samples.…”
Section: Methodsmentioning
confidence: 99%
“…Other authors have also reported that, because of the genetic variability between strains, using a single strain genome as reference genome lacks accuracy [95][96][97]. This MTBC-wide pangenome approach has been suggested before, including for other organisms [38,47,[95][96][97][98][99][100]. However, such an approach also has its own drawbacks, including difficulty in mapping reads that bridge the boundaries between accessory genes and the rest of the genome, comparing strains of different lineages including phylogenetic analyses and retention of gene names and codes in clinical use, where H37Rv is deeply embedded [89].…”
Section: Size Co-ordinates In H37rvmentioning
confidence: 97%